(untitled) (Technological Innovations Journal, 2022)
The excessive use of online video games by adolescents has caused problems in family, academic, physical and psychological contexts, for this reason specialists have set their sights on this situation, to the point that in 2021 it is integrated into the international classification of diseases 11th edition (ICD-11) as a disorder due to addictive behaviors. Being a relatively new topic, it becomes necessary to know the profiles, characteristics and situations that influence video game use disorder in adolescents, in order to build knowledge of the phenomenon that allows the structuring of prevention programs. For this reason, a systematic search is carried out in the primary research sources stored in the databases, in addition to the use of the most recognized search engines. This grouping and selection of information allows us to conclude that the predisposition to disorder due to the use of online or offline video games is to be a man, maintain a great exposure to the activity of the game, have a bad attitude towards the school environment, poor school performance, make great use of games called MMORPGs, prefer online games instead of physical and social activity.